Reference intervals for growth arrest-specific 6 protein in adults - AY, NADİYE PINAR; BİNGÖL ÖZAKPINAR, ÖZLEM (TAYLOR & FRANCIS LTD, 2017)
The objective of this study was to establish reference intervals for growth arrest-specific 6 (GAS6), a vitamin K-dependent protein, in human adult plasma according to the Guideline of Clinical and Laboratory Standards Institute (CLSI) C28-A3. Blood samples were collected from 308 healthy volunteers aged 18-72 (157 female, 151 male). A non-parametric approach was used to calculate the reference interval. The plasma GAS6 reference interval was determined, with 90% confidence interval: the lower limit (2.5 percentile) was 2.5 (1.9-3.1) g/L and the upper limit (97.5 percentile)=18.8 (18.0-22.3) g/L. Harris-Boyd's test did not suggest partitioning by age or gender: medians for males [7.8 (5.8-10.7) g/L] and females [9.9 (7.1-13.5) g/L]. Three age-subgroups were tested: 18-29 years (n=168); 30-44 years (n=73); 45-72 years (n=67). The intra- and inter-assay variations were 12.6% (mean, 5.2 +/- 0.7g/L) and 14.0% (mean, 9.2 +/- 1.3g/L), respectively. The mean recovery was 104%. This study reports plasma GAS6 reference intervals established first according to the guideline of CLSI C28-A3.
Keywords: Biochemical marker; clinical and laboratory standards nstitute; enzyme-linked mmunosorbent assay; GAS6; international federation of clinical chemistry; reference ranges; Vitamin K; RECEPTOR TYROSINE KINASE; LABORATORY REFERENCE INTERVALS; VASCULAR SMOOTH-MUSCLE; K-DEPENDENT PROTEINS; PLASMA-CONCENTRATIONS; GAS6 CONCENTRATIONS; AXL; CELLS; EXPRESSION; LIGAND